Analisa Produktifitas Alat Berat Pada Pekerjaan Timbunan Tanah Dan Perkerasan Berbutir Studi Kasus Jl.Kampus UNRI - Fikhri Abdi Digdaya; Dwi Visti Rurianti; Sri Djuniati; Horas Saut MM; M M Shalahuddin; Haji Gussyafri (Teknik Sipil Universitas Riau, 2025)
This study analyzes the productivity of heavy equipment used in embankment and granular pavement works on Jalan Kampus Universitas Riau. The efficiency of heavy equipment utilization plays an important role in determining project duration and operational costs in road construction. This research compares two alternatives of heavy equipment usage: the configuration applied by the project contractor and an alternative proposed by the author. The methodology includes field observations, primary and secondary data collection, and quantitative analysis of equipment productivity, work duration, and operational costs. The results show that the productivity of field equipment includes an Excavator CAT 320 GX of 90.888 m³/hour, Dump Truck Mitsubishi FE SHD 136PS of 2.452 m³/hour, Motor Grader CAT 120 of 554.850 m²/hour, Vibratory Roller SAKAI SV526 of 255.15 m²/hour, Water Tank Truck Mitsubishi Colt Diesel FE 74 HD of 97.2 m³/hour, and Bulldozer CAT D4C of 37.583 m³/hour. The total project duration is 65 working days with an operational cost of Rp2,898,885.96 per hour. Comparative analysis indicates that the alternative equipment configuration offers better time and cost efficiency, making it suitable as a reference for similar projects.